STRATEGI KOMUNIKASI INTERPERSONAL KEPALA DESA DALAM UPAYA PENCEGAHAN COVID-19 DI DESA KALIAMAN KECAMATAN KEMBANG KABUPATEN JEPARA - Murniati Murniati; Muqodim Muqodim (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2021)
This research is motivated by the increasingly widespread spread of the Covid-19 virus, resulting in restrictions on interacting. Based on these problems, the Kaliaman Village Head took follow-up actions in preventing Covid-19 through interpersonal communication strategies. Interestingly, in this case, what interpersonal communication strategy does the Village Head do to the community. Therefore, it is appropriate to conduct a research entitled